Upaya Mengatasi Prilaku Perundungan Dikalangan Siswa Melalui Optimalisasi Program Sekolah Ramah Anak Di SMP Negeri 10 Kota Bengkulu - Dinasti, Dinasti; Syarkati, Syarkati (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This study investigates efforts to address bullying behavior among students through the optimization of the child-friendly school program at SMP Negeri 10 Bengkulu City. The aim of this study is to identify the forms of bullying, the efforts taken by the school, and the actions implemented. This is a qualitative research. Data collection was conducted through observation, interviews, and documentation. The findings indicate that forms of bullying among students at SMP Negeri 10 include physical fights involving hitting and kicking, insulting peers by mocking their parents' names, drawing on peers' faces, mocking teachers, spreading false information, and shouting at fellow students. Contributing factors to bullying behavior may include lack of affection, family issues, peer pressure, being a victim of a broken home, and poor family communication. The school's efforts at SMP Negeri 10 Bengkulu City include implementing government programs to handle bullying cases. Homeroom teachers or counseling teachers first summon the students involved for guidance and counseling. Parents are then called in to inform them of their child's behavior at school. This policy has proven effective—parents continue to respond and take responsibility for their children’s actions. Additionally, the school organizes socialization sessions for both perpetrators and victims, including counseling and presentations from police officers to emphasize that bullying is harmful. Classrooms are equipped with posters and reading corners. To optimize the program, agreements are made between the school, parents, and the government for follow-up actions on bullying cases.